Ted Williams : a baseball life - Seidel, Michael (Chicago, IL Contemporary Books, 1991)
An account of one of baseball's greatest hitter and the era in which he played
D., 4/04
Keywords: William, Ted, 1918-; Baseball players--United States--Biography; Boston Red Sox (Baseball team)